What is equality? - Adachi, Hidehiko (2025)
This article offers a critical analysis of the concept of equality, exploring its multiple interpretations and key distinctions within Western thought. It seeks to clarify conceptual ambiguities that often hinder constructive debate on social justice. Two main forms of equality are discussed: simple equality, which assumes identical treatment regardless of differences, and proportional equality, which allocates resources based on relevant attributes such as effort, need, or ability. Drawing on Aristotle’s philosophy and modern developments, we examine how both notions coexist and interact, especially in contexts of distributive justice. The paper also explores normative principles used to justify social distributions: contribution, need, benefit, and capacity. It argues that clarifying these categories enables partial consensus on fairness, crucial for designing equitable public policies. The article combines philosophical depth with practical relevance, offering a useful framework for navigating contemporary challenges related to equity and justice.